Practical aspects of the polymodel approach to the synthesis of mechatronic modules of packaging equipment - Savchuk, Oleksandr; Kyrylchuk, Yevhenii; Kostіn, Volodymyr (My University, 2024)
The poly-model approach to the synthesis of mechatronic modules for packaging equipment allows us to flexibly and efficiently design and manufacture packaging machines that meet the changing needs of the market and provide high performance, reliability and cost-effectiveness

Полімодельний підхід до синтезу мехатронних модулів пакувального обладнання дозволяє нам гнучко і ефективно проектувати і виготовляти пакувальні машини, які відповідають мінливим потребам ринку і забезпечують високу продуктивність, надійність і економічну ефективність
Keywords: кафедра мехатроніки та пакувальної техніки; рractical aspects; polymodel approach; synthesis; mechatronic modules; packaging equipment; практичні аспекти; полімодельний підхід; синтез; мехатронні модулі; пакувальне обладнання